A hybrid SATS algorithm-based optimal power flow for security enhancement using SSSC. (10th March 2021) - Cherukupalli, Kumar; Chinda, Padmanabha Raju; Peddakotla, Sujatha
Security and performance of the power system is the prime concern in its planning and operation. It is essential to devise proper measures for maintenance and improvement of security in the power system. Static synchronous series compensator (SSSC) is a type of series flexible AC transmission system device. The present research proposes a hybrid simulated annealing and Tabu search (Hybrid SATS) algorithm with SSSC to solve security constrained optimal power flow problems. The primary objective of the research work is to enhance the security of the power system and minimise the generator fuel cost. Contingency ranking is used to select line outages. The line flow limit violations in various single line outages are relieved effectively by Hybrid SATS with SSSC method, which keeps power flows within their security limits. Simulation studies are carried out on standard IEEE 30 bus to identify effectiveness of the proposed hybrid method and the obtained outcomes are put in comparison to SA with SSSC and TS with SSSC methods.